2018
DOI: 10.1016/j.jadohealth.2018.04.010
|View full text |Cite
|
Sign up to set email alerts
|

Polytobacco Use Among a Nationally Representative Sample of Adolescent and Young Adult E-Cigarette Users

Abstract: Just over half of ENDS users also used other tobacco products, increasing their risk for nicotine addiction and other health harms. The Food and Drug Administration is responsible for communicating product risk to consumers and should consider common patterns of use and relative risk perceptions in its ENDS public education efforts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
39
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 32 publications
3
39
1
Order By: Relevance
“…Furthermore, research about polytobacco use among North American adolescents found that 81% of e-cigarette users also used at least one other tobacco product [35]. In a similar study among North American adolescents and young adults, 55.9% were classified as polytobacco users [36]. The results of the present study are also consistent with previous research among North American young adults that reported using at least two tobacco products, with shisha being the most common, followed by regular cigarettes and e-cigarettes [37].…”
Section: Discussionmentioning
confidence: 95%
“…Furthermore, research about polytobacco use among North American adolescents found that 81% of e-cigarette users also used at least one other tobacco product [35]. In a similar study among North American adolescents and young adults, 55.9% were classified as polytobacco users [36]. The results of the present study are also consistent with previous research among North American young adults that reported using at least two tobacco products, with shisha being the most common, followed by regular cigarettes and e-cigarettes [37].…”
Section: Discussionmentioning
confidence: 95%
“…Available longitudinal evidence suggests that, after controlling for observables, youth who reported using e-cigarettes were no more likely to use cigarettes 1 year later than youth who did not use e-cigarettes (Conner et al 2018). About half of e-cigarette users jointly used cigarettes (11.5%), cigars (7.7%), and cigars and water pipes (5.2%) (King et al 2018). Using data from five nationally representative cross-sectional surveys, Levy et al (2019) find associations that suggest that youth are substituting e-cigarettes for cigarettes.…”
Section: Patterns Of "Polytobacco" Consumption and Substitutionmentioning
confidence: 99%
“…7 Youth were more likely to explore different tobacco products. [8][9] Over 80% of poly-tobacco product users reported starting concomitant use in young adult age (aged 18-35) 10 and continued to use in lives. 8 Most research on PTU was conducted in western countries (e.g.…”
Section: Introductionmentioning
confidence: 99%